HISTORICAL AND CULTURAL PROBLEMS AND PERSPECTIVES OF HUMANITARIAN SECURITY OF UKRAINE - Чупрій, Л. В. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
In the article the state of humanitarian safety of Ukraine is analysed and recommendations are offered in relation to the increase of efficiency of legal, moral, religious mechanisms of realization of humanitarian safety.